O imaginário e a representação de Curitiba na obra de Dalton Trevisan - Oliveira, Enio Alves de (2011)
The objective of this study is to investigate the construction of the imaginary universe and the Curitiba representation, at Dalton Trevisan`s Masterpiece writer, who was born on June 14 th, 1925 in Curitiba, Paraná, city of his hometownresidence. This reseach unites themes and images that highlights the relation between tale and imaginary, the word and silence, the dream, the inspiration, the childhood, the memory, the time, the imagination, the duplicity, the enchantment, and the care he demonstrates for the city of Curitiba. The writer is known and recognized nationally and internationally, he is one of the greatest Brazilian storytellers. The bibliography research is based on authors that deal with themes related to imaginary, tale, the city and its development. Among the related authors are: Gilbert Durand, Gaston Bachelard, Mempo Giardinelli, Antonio Candido, Mikhail Bakhtin, Otávio Paz, Italo Calvino, Cristóvão Tezza, Hegel, Adorno, Aristóteles, Jorge Luis Borges, Marc Augé, Nelson Brassic Peixoto, Sérgio Rivero, Ricardo Piglia and others. The dissertation is divided in three chapters and in each one of then it was tried to make a division between the theoretical references and the tales from the themes chosen from Dalton Trevisan s work. In the first chapter it is discussed how to build the imaginary universe and fictional narrative in Dalton Trevisan`s work, seeking to understand his imaginary world which enables the creation of great stories. It also aims to verify how the poetic construction and it`s images occur and how the lyricism in the narrative of Trevisan`s work appears, noticing how the author writer the same work in prose and verse, the short narratives, the images of human degradation, the poetic and the approach to the tale. The second chapter analyzes the images of Curitiba, the imaginary and fictional of the author. We also emphasize, Curitiba: the transcribed scene, the notion of the picture of the reality, and that Curitiba is very present at Trevisan s Literature, comparing past, present and future. The third chapter, approaches the social imaginary and mythical, observing how to build the imaginary networks from the perspective of Dalton Trevisan, in the social context and insertion of myths like: Narciso, Penélope, the Vampire s myth, to establish a relation with his work. There is also an especial focus on question of symbolic imagination and how the house is designed on his fictional narrative. There are, in diverse chapters, relevant themes which are dealt in his work such as sex and violence, issues present at many of his tales.